SISTEM INFORMASI PENGENDALIAN PIUTANG TAK TERTAGIH PERUSAHAAN MANUFAKTUR: (System Information Control Uncollectible Accounts Receivable in Manufacturing Companies) - Putri Nilasari, Ayunda; Retnosari, Retnosari (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This research was conducted at PT. Hisheng Luggage Accessory Semarang, located at Jl. Gatot Subroto no.02 Kawasan Industri Candi blok 23 no. 6 C Ngaliyan, Semarang. This company engaged in manufacturing. Manual managing receivables seems not efficient. There was no grouping performance of uncollectible accounts, so the obstacles in the settlement of uncollectible accounts still found. The obstacles during grouping the performance of account receivables caused late billing process which also impacted to the payment of uncollectible receivables was not smoothly done. To overcome this problem, the authors build " information accounting system for accounts receivable control with the age of web-based receivables method at PT. Hisheng Luggage Accessory "which is effective for making decisions and is efficient in managing accounts receivable, one of which is by warning of receivables due date and groupings the receivables which simplify the management of accounts receivable. The system uses Bootstrap programming language, HTML and PHP5 with a database using MySQL. Data obtained through literature study, observation and interviews. This research generating an account receivable accounting information system that has a warning of due dates and a grouping of accounts receivable that makes it easy to manage accounts receivable and reports integrated with the system. Keywords: Accounting information systems, Accounts Receivable. The Receivable Age Method